Zoeal stages and megalopa of Mithrax hispidus (Herbst, 1790) (Decapoda: Brachyura: Majoidea: Mithracidae): A reappraisal of larval characters from laboratory cultured material and a review of larvae of the Mithrax-Mithraculus species complex - Santana, William [UNESP]; Pohle, Gerhard; Marques, Fernando (Taylor & Francis, 2003)
Mithrax hispidus (Herbst, 1790) is a mithracid majoid crab occurring on sand, corals and rocks in waters of the western Atlantic. Larval development consists of two zoeal stages and a megalopa. All larval stages are described in detail based on multiple cultures. Prior to this study, larvae of M hispidus were considered to be different and grouped separately from most other larvae of Mithrax, primarily based on setation. A detailed morphological examination, based on the same specimens used for the first description, revealed that the inclusion of M hispidus in a separate group is not valid as zoeae now fully agree with the morphological characteristics defined for the other group of five Mithrax species, including M. pleuracanthus, M. verrucosus, M. caribbaeus, M. coryphe, and M. forceps. This illustrates the importance of precisely recording morphological details such as setation, which may otherwise lead to incorrect interpretations with regard to perceived taxonomic affinities. A comparison of larvae of the Mithrax -Mithraculus species complex does not support separation into two genera. Larval evidence supports the recently suggested adult-based synonymization of M caribbaeus with M. hispidus.
Keywords: Larval development; Majoidea; Mithracidae; Mithrax hispidus; Systematics; Anthozoa; Brachyura; Decapoda (Crustacea); Invertebrata; Mithraculus; Mithraculus coryphe; Mithraculus forceps; Mithrax; Mithrax coryphe; Mithrax verrucosus